PAHAM KEAGAMAAN LOKAL (Studi Kasus Di Kasepuhan Ciptagelar) - Nuhrison M.Nuh (Harmoni, 2013)
The aim of this research are describing the relationship between the member of local religion with the state interests which embodied in policy and program as well as services and fulfillment of the citizenship rights in the administration of population. Specifically, this research sought to (a) exploring the existence of a local religion ideology and its adherents; (b) parsing and maping their social dynamics when they dealing with other identity and faiths, and (c) explaining and analyzing the factual situation regarding to services of population administration which influence to the right of citizenshipp, especially for local religion.